Social Determinants of Learning: Implications for Research, Policy, and Practice - Meira Levinson; Alison K. Cohen (SAGE Publishing, 2023)
The COVID-19 pandemic revealed what educators, policymakers, and researchers have long known-namely, that learning opportunities and outcomes are intimately intertwined with other aspects of children's and families' lives. The list of social forces outside the education sector that can affect learning is endless and includes economic experiences that are inequitably distributed, such as housing security (Gallagher et al., 2020), income (Hoynes & Rothstein, 2019), and wealth (Pfeffer, 2018), as well as social experiences, such as interpersonal and structural racism, (dis)ability, and xenophobia (Anderson-Nathe, 2020; DeMatthews, 2020). Now, it is time to lock in this learning among policymakers, practitioners, and researchers. We posit that the concept of "social determinants of learning" can serve as a powerful reframing tool for promoting educational equity, similar to the conceptual shift and policy impact we have seen in public health as "social determinants of health" has become an accepted and eventually essential concept.